The The Evaluation of School Operational Assistance (BOS) In Management Quality of Primary Education in Gugus Dewi Sartika (Educational Management, 2022)
The purpose of this study is to explain the planning and management of primary school BOS funds, in accordance with established regulations, in order to achieve national standards for school education and the government’s goal of allocating BOS funds. An important factor in improving the quality of education is sufficient education funding. The implementation of 12-year compulsory education is expected to increase access through BOS funds by the community, as well as provide more benefits to people who do not receive educational services. This research is to understand and analyze the effectiveness of school operational assistance funds (BOS) in the quality management of elementary school education in the Gugus Dewi Sartika, Bergas District, Semarang Regency. This research uses qualitative research that aims to explain the phenomenon in depth through data collection. Therefore, in this study, the problem of data depth (quality) is emphasized more than the amount of data (quantity). This study uses a multi-case design where this research is used to understand the similarities and differences between several cases studied. There is a priority plan in the school activity budget plan (RKAS), using the BOS budget that has been analysed. The use of the BOS budget is planned, and in the implementation of the budget, the BOS budget is used as planned, and has also succeeded in achieving diverse results, the improvement of students, educators, and school achievements, and a well-organized school environment for improving the quality of basic education in the Gugus Dewi Sartika, Bergas district, Semarang Regency.